CD19 CAR-T Cells With Membrane-Bound IL-15 for B-Cell Acute Lymphoblastic Leukemia After Failure of CD19 and CD22 CAR-T Cells: Case Report - Sun, Yao; Su, Yongfeng; Wang, Yizhi; Liu, Na; Li, Yuhang; Chen, Jianlin; Qiao, Zhuoqing; Niu, Jingwen; Hu, Jiangwei; Zhang, Bin; Ning, Hongmei; Hu, Liangding (Frontiers in Immunology, 2021)
Objectives: At present, re-infusions of chimeric antigen receptor (CAR)-T cell have exhibited limited efficacy, while their efficacy on extramedullary relapse remains to be further elucidated in B-cell acute lymphoblastic leukemia (B-ALL). Although combination with IL-15 demonstrated the potential to enhance anti-tumor activity of CAR-T, the efficacy of this approach remains to be validated clinically. Methods: We reported a patient with B-ALL with extramedullary relapse after allogeneic stem cell transplantation and who was resistant to chemotherapy and radiotherapy. In total, he received four treatments with CAR-T cells repeatedly under the status of disease progression. Results: First, the patient received autologous murine CAR19-CD28-CD3ζ-T cells and achieved full resolution of extramedullary leukemia lasting eight months. After systemic disease relapse, he received autologous humanized CAR22-41BB-CD3ζ-tEGFR-T cells and achieved complete remission (CR) with incomplete blood count recovery (CRi) with minimal residual disease (MRD) negativity in the bone marrow and shrinkage of extramedullary leukemia. Over two months later he experienced a relapse of the systemic disease, and he received autologous murine CAR19-41BB-CD3ζ-mIL15-T cells and achieved CRiMRD- lasting five months with the strongest expansion and persistence of CAR. Finally, on relapse of CD19- medullary disease, he received allogeneic humanized CAR22-41BB-CD3ζ-tEGFR-T cells but only achieved a transient decrease in the number of blasts. No CAR-T cell-related encephalopathy syndrome was observed and all side effects were manageable. Conclusion: Our report hints the feasibility and safety of CD19 CAR-T cell expressing membrane-bound IL-15 for patient with B-ALL even if relapsed after multiple CAR-T cells therapies.